Measurement of temperature rises in the femtosecond laser pulsed three-dimensional atom probe - Cerezo, A; Smith, G; Clifton, P (American Institute of Physics, 2006)
A previous Letter [B. Gault et al., Appl. Phys. Lett. 86, 094101 (2005)] interpreted measurements of the field evaporative enhancement under femtosecond pulsed laser irradiation of a field emitter in terms of a direct electric field enhancement by the intrinsic field of the laser light. We show that, on the contrary, the field evaporation enhancement is predominantly a thermal heating effect. Indirect measurements of the peak specimen temperature under irradiation by femtosecond laser pulses are consistent with temperature rises obtained using longer laser pulses in a range of earlier work.